Uji Toksisitas Subkronik Ekstrak Etanol Daun Sidaguri (Sida Rhombifolia L.) Terhadap Fungsi Hati dan Ginjal Pada Tikus: Subchronic Toxicity of Ethanol Extract of Sidaguri Leaves (Sida Rhombifolia L.) on Liver and Kidney Function in Rats - Kharina Septi Lestari; Aulia Nurfazri Istiqomah; Reza Pratama; Boy Ignatius Simamora; Anissa Nadya Oktriyani (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2025)
Sidaguri leaves (Sida rhombifolia L.) have been widely used in traditional medicine due to their anti-inflammatory, diuretic, and analgesic properties. To ensure their safety, a subchronic toxicity study was conducted using ethanolic extracts of Sida rhombifolia leaves. The study involved male and female Wistar rats administered a dose of 14 mg/kg body weight (BW) daily for 90 days. Toxic symptoms were observed throughout the study period, followed by organ weight assessment, blood biochemical analysis (SGOT, SGPT, creatinine, and urea), and histological examination of heart and kidney tissues. The results showed no toxic symptoms or mortality in the test animals. Levels of SGOT, SGPT, creatinine, and urea remained within normal limits, with no statistically significant differences (p>0.05) between the control and treatment groups. Histological analysis revealed no signs of necrosis in heart and kidney tissues. In conclusion, the ethanolic extract of Sida rhombifolia leaves at a dose of 14 mg/Kg BW is non-toxic and considered safe for daily consumption. Keywords: Sidaguri leaves; Subchronic toxicity; Histologic; Liver; Kidney.